Ultrazvočne značilnosti maternice in jajčnikov pri ženskah z zgodnjimi spontanimi splavi - Eržen, Petra (Medicinski razgledi, 2004)
In 71 women with clinically confirmed early spontaneous abortions we wanted tofind the ultrasound detectable morphological abnormalities of uterus and ovaries and to establish the frequency of these anomalies. For the detection of all morphological abnormalities we used a 7-MHz vaginal ultrasound probe Bruel and Kjaer in the luteal phase of the cycle. 23 (32.4%) of investigated women had normal ultrasound findings and 48 (67.6%) had pathological ones. Among the morphological abnormalities of uterus, 30 (42.3%) had minor or majorcongenital malformations and 7 (9.9%) had uterine fibroids. Among the morphological abnormalities of ovaries, 25 (35.2%) had polycystic ovaries and 3 (4.2%) had ovarian cysts. 15 (21.1%) of all investigated women had a combination of congenital uterine malformation and polycystic ovaries. Morphological abnormalities of the uterus and the ovaries represent without doubt an important and great risk factor for impaired pregnancy outcome. Congenital uterine malformations are important also in etiology of early spontaneous abortions and not only in the etiology of late spontaneous abortions and preterm delivery. Not only polycystic ovary syndrome but also polycystic ovaries are frequently found in women with early spontaneous abortions. A simultaneous occurence of congenital uterine malformation and polycystic ovaries, found in 15 (21.1%) of women, confirmed the previous clinical observations.
Keywords: Abortion, Habitual; Jajčnik, ciste; Maternica; Etiology; Policistični jajčnik, sindrom; Uterus; Abnormalities; ginekologija; jajčniki; Ultrasonography; ultrazvočna diagnostika; Ovarian Cysts; abortus; Polycystic Ovary Syndrome; Abortus habitualni